Od starega zdravila do nove protimikrobne indikacije - Frlan, Rok (Farmacevtski vestnik, 2021)
Antimicrobial resistance is one of the greatest threats to global public health today. A possible therapeutic strategy in the fight against microorganisms is to find new uses for approved or investigational drugs that are outside the scope of their original medical indication. Drug repurposing is a much cheaper and shorter alternative as compared to the typical route for de novo drug development. Despite many major advantages of drug repurposing, there are only a few success stories in the field of antimicrobials. A possible reason for that may lay in high prices of clinical trials, intellectual property laws, and the establishment of adequate pharmacokinetic and pharmacodynamic properties. In general, there are three basic methods that are used in drug repurposing research, phenotypic screening, computer-based methods and serendipitous observations. Because of the increased interest in drug repurposing, a significant increase of new antimicrobial drugs can be expected in the future.
Keywords: Antibiotiki; nova indikacija starega zdravila; odpornost; preizkušanje učinkovin; protimikrobna zdravila